University Students’ Perception towards Online Learning: Synchronous and Asynchronous - Nor, Hidayah; Wijaya, Muhammad Sayid (SALEE: Study of Applied Linguistics and English Education, 2023)
The teaching and learning process in universities around Indonesia has immensely transformed due to the covid-19 pandemic, including in UIN Antasari Banjarmasin and UIN Raden Intan Lampung. This demands lecturers to adapt their teaching to online learning, either synchronous or asynchronous. However, these two variations of learning alter students’ views on how learning should be experienced which further influences their learning performance. Thus, this research is aimed at finding out English Language Education students' perception towards online learning: Synchronous and Asynchronous. This research is descriptive quantitative. There is an e-questionnaire of students’ perception consists of 6 items for Perceiver, 6 items for Object/Target, 6 items for Context. The data obtained from the questionnaire has been analyzed by using descriptive statistics and interpreting the Likert Scale of students’ answers (Strongly Agree, Agree, Disagree, and Strongly Disagree). The finding showed that the students' perceptions were positive in terms of Learning platforms, Learning Materials, and Learning Activities in online learning both Synchronous and Asynchronous.